Using Eye-Tracking to Investigate an Activation-Based Account of False Hearing in Younger and Older Adults - Failes, Eric; Sommers, Mitchell S. (Frontiers in Psychology, 2022)
Several recent studies have demonstrated context-based, high-confidence misperceptions in hearing, referred to as false hearing (Failes et al., 2020; Rogers et al., 2012; Sommers et al., 2015). These studies have unanimously found that older adults are more susceptible to false hearing than younger adults, which the authors have attributed to an age-related decline in the ability to inhibit the activation of a contextually predicted (but incorrect) response. However, no published work has investigated this activation-based account of false hearing. In the present study, younger and older adults listened to sentences in which the semantic context provided by the sentence was either unpredictive, highly predictive and valid, or highly predictive and misleading with relation to a sentence-final word in noise. Participants were tasked with clicking on one of four images on screen to indicate which image depicted the sentence-final word in noise. We used eye-tracking to investigate how activation, as revealed in patterns of fixations, of different response options changed in real-time over the course of sentences. We found that both younger and older adults exhibited anticipatory activation of the target word when highly predictive contextual cues were available. When these contextual cues were misleading, younger adults were able to suppress the activation of the contextually predicted word to a greater extent than older adults. These findings are interpreted as evidence for an activation-based model of speech perception and for the role of inhibitory control in false hearing.